Against COVID-19 Pandemic: Bibliometric Assessment of World Scholars' International Publications related to COVID-19 - Dono Darsono; Jajang A Rohmana; Busro Busro (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2020)
This article focuses on sharing information and knowledge in the form of scholars’ academic communication about the COVID-19 epidemic in international publications. The data was collected from search results in the Scopus database from December 2019 to March 2020. Through the bibliometric assessment method, the survey shows that there are 1475 publications on COVID-19. There are 1104 publications (75%) that can be accessed. Although COVID-19 has started about four months since the first case in Hubei China (11/17/20), scholars are making a research program and publish their findings in order to share information and knowledge in dealing with the pandemic. The sharing information is theoretically a form of world scholarly academic communication activities. Therefore, open access publications can help scholars to easily communicate and share information about their findings. This then affects the number of publications and citations with the capacity of research institutions, sponsors, and countries. This article recommends as broad as possible to provide open access in the midst of disaster situations in order to handle COVID-19 pandemic faster and easier.